Risk Factors of Stunting in Toddlers in the Work Area Health Center Bone Rombo - Wa Ode Sriy Hastuti (Universitas Mandala Waluya, 2021)
The incidence of stunting in toddlers aged 24-59 months at the Bone Rombo Health Center in 2018 was 18.12% and in 2019 it was 19.01%. The study aims to determine the risk factors for stunting in children aged 24-59 months in the work area at the Bone Rombo Health Center. This research is a quantitative research with Case-Control design. The population in this study were 45 children under five with a sample size of 31, with a comparison of the case sample and control sample 1:1. Data collection through microtoice measurements and scales, as well as questionnaires. Analysis using the Odds Ratio test. The results showed that nutritional status with an OR value=5.769, birth weight with an OR value=6.314, breastfeeding status with an OR value=4.552, family economic status obtained an OR value=4.444. The conclusion of the study is that nutritional status, birth weight, breastfeeding status, and economic status are risk factors for stunting in children aged 24-59 months at the Bone Rombo Health Center. It is recommended for parents to always pay attention to the nutritional balance for children through fulfilling nutrition from an early age starting from the mother's pregnancy and giving exclusive breastfeeding to prevent stunting.